Comparing the Superficial Vasculature of the Central Nervous System in Six Laboratory Animals: A Hypothesis About the Role of the "Circle of Willis". Issue 11 (27th May 2019) - Kim, Yoo Yeon; Chao, Janet Ren; Kim, Chulho; Jung, Harry; Kim, Boyoung; Kang, Tae‐Cheon; Chang, Jiwon; Park, Hae Sang; Suh, Jun‐Gyo; Lee, Jun Ho
ABSTRACT: We provide images of the entire central nervous system vasculature, and compare the anatomical findings in six different laboratory animals. A detailed understanding of the specific anatomy for each is important in the design of experimental modeling and for understanding the specific function of each target organ. Six different types of animals, the Korean wild mouse, C57BL/6J mouse, F344 rat, mongolian gerbil, Syrian hamsters, and guinea pigs, were included. To stain the blood vessels in each of the animals, Alcian blue reagent was used to perfuse each species. The bifurcation and anastomotic patterns of the anterior cerebral arteries differed in each species. The vascular supply to the olfactory nerve was visualized as a single artery supplying both olfactory nerves, and arteries supplying the lateral portion of the olfactory nerves originating from the olfactory bulb area. The posterior communicating arteries of the six animals demonstrated unique morphologies. The shape of the hypophyseal portal system varied by species. Most animals used in this study had a hexagonal Circle of Willis, except for the Korean wild mouse. Using this approach, we successfully mapped the brain vascular system in six different species of animals. This information and the images created can guide other researchers as they design research studies and create experimental models for new surgical procedures and approaches. Anat Rec, 2019. © 2019 Wiley Periodicals, Inc. Anat Rec, 302:2049–2061, 2019. © 2019 American Association for Anatomy